Plataforma Moodle y su repercusión en el rendimiento académico en estudiantes en la asignatura de matemáticas”. - Quingla, Jimmy J. (2022)
This investigation has as purpose to determine how it implies in the uses of digital tools like teaching resources in the Institutional platform Moodle in students from Third Baccalaureate Science at the Sarance Educative Unit for improving the academic performance in math subject. The studies will develop with quantitative focus of field design since the sample consisted of 42 students investigated in the classroom where it applied a survey with a questionnaire of 20 questions to get the real data; the analysis of data took place a correlational study with the main goal to know the relation that exist between Moodle platform variables and academic performance. These data’s were organized through Microsoft Excel then be processed and used the SPSS version 25.0, like Cronbach alpha, Shapiro- Wilk and Rho Spearman where let to know that existed a positive relation between variables. Therefore, the uses of digital tools like teaching resources in Moodle Institutional platform helps in the teaching learning process of students and improving the academic performances. In conclusion, the non uses of digital tools like teaching resources in Moodle Institutional platform due to different facts have affected the academic performances in math subject.